Amorphous Ionic Polymers with Color‐Tunable Ultralong Organic Phosphorescence. Issue 52 (27th November 2019) - Wang, He; Shi, Huifang; Ye, Wenpeng; Yao, Xiaokang; Wang, Qian; Dong, Chaomin; Jia, Wenyong; Ma, Huili; Cai, Suzhi; Huang, Kaiwei; Fu, Lishun; Zhang, Yanyun; et al.
Abstract: Amorphous purely organic phosphorescence materials with long‐lived and color‐tunable emission are rare. Herein, we report a concise chemical ionization strategy to endow conventional poly(4‐vinylpyridine) (PVP) derivatives with ultralong organic phosphorescence (UOP) under ambient conditions. After the ionization of 1, 4‐butanesultone, the resulting PVP‐S phosphor showed a UOP lifetime of 578.36 ms, which is 525 times longer than that of PVP polymer itself. Remarkably, multicolor UOP emission ranging from blue to red was observed with variation of the excitation wavelength, which has rarely been reported for organic luminescent materials. This finding not only provides a guideline for developing amorphous polymers with UOP properties, but also extends the scope of room‐temperature phosphorescence (RTP) materials for practical applications in photoelectric fields. Abstract : All the colors of the rainbow : Ultralong organic phosphorescence (UOP) was enabled in a set of amorphous polymers by ionization under ambient conditions. The UOP emission color could be controllably manipulated from blue to red over the entire visible region (see photographs) by varying the excitation wavelength.